The Drosophila Tumorous-lethal hematopoietic oncogene is a dominant mutation in the hopscotch locus. - Hanratty, W.P.; Dearolf, C.R. (Molecular and General Genetics, 1993)
The Drosophila Tumorous-lethal (Tum-l) mutation acts as an activated oncogene, causing hematopoietic neoplasms, overproliferation, and premature differentiation. Tum-l is a dominant mutation in the hopscotch (hop) locus, which is required for cell division and for proper embryonic segmentation. The Tum-l temperature-sensitive period for melanotic tumor formation includes most of larval and pupal development.